COMPARATIVE ANALYSIS OF STUDENTS' CRITICAL THINKING ABILITIES BETWEEN OUTDOOR AND INDOOR LEARNING - Manap, Abdul (An-Nahdlah: Jurnal Pendidikan Islam, 2023)
The aim of this research is to determine the comparison of students' critical thinking abilities who use outdoor and indoor learning methods with conventional learning methods. The method used in this research is a quantitative method with an experimental type. The analysis used in this research is a comparative test with the Independent sample T-test formula. The results of the trials that have been carried out provide the conclusion that the use of the Outdoor Learning learning model convincingly shows a significant influence on the Critical Thinking Ability of students at SMP N Satap Satu Pringgasela. The significance value (2-tailed) is 0.01, which is smaller than the alpha value (0.05), indicating that there is a significant difference between the group that used the Outdoor Learning learning method and the control group. By rejecting the null hypothesis (Ho) and accepting the alternative hypothesis (Ha), it can be concluded that the use of the Outdoor Learning learning model has a significant impact on increasing the Critical Thinking Ability of students at SMP N Satap Satu Pringgasela.